PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN - Verra Ayu Dyan Anggraeni, 09.05.51.0053; Irsyad, Moch. (Students Journal of Economic and Management, 2013)
The financial manager is obliged to make financial decisions that consists of investment decisions, financing decisions, and dividend policy. The right financial decisions to maximize the value of the company (corporate objectives). Optimization of corporate value is obtained, among others, by implementing financial management functions, in which a financial decision affects the others, which eventually affects the corporate value. This research aimed to analyze the effect of investment, funding decisions and dividend policy on the manufacture firm value listed in the Indonesia Stock Exchange. The variables observed in this study consisted of investment decision (X1), funding decisions (X2), dividend policy (X3) and the value of the company (Y). The population used as the object of study is a report of a manufacturing company that went public and listed on the Indonesia Stock Exchange in 2008-2010. The sampling technique used was purposive sampling method. The results of this research indicate that the investment decisions positively affects the firm value, financing decisions did not significantly affects the firm value. While the dividend policy positively affects the firm value.Key words: investment decisions, funding decisions, dividend policy, corporate value.